Possible toxic metal exposure of prehistoric bronze workers. Issue 10 (October 1987) - Harper, M
Abstract : An attempt has been made to assess the possible occupational exposure to arsenic, lead, and mercury during the Bronze Age. Archaeological, metallurgical, and historical evidence is combined to form a picture of the potential toxic hazards. In the case of arsenic a definite picture emerges of the effect of toxicity as a useful material is abandoned for health reasons on discovery of an acceptable alternative.